x+2y+2z=3. 2x-2y-z=3. x-2z=-5
1 answer:
Answer:
x = 1, y = -2, z = 3.
Step-by-step explanation:
x + 2y + 2z = 3 A
2x -2y - z = 3 B
x - 2z = -5 C
If we add equations A and B we eliminate y:
3x + z = 6 E
Multiply E by 2 :
6x + 2z = 12 F
Adding C and F we get:
7x = 7
x = 1.
Plug this into equaton C:
1 - 2z = -5
-2z = -5 - 1 = -6
z = 3.
Now plugging x = 1 and z = 3 in equation A:
1 + 2y + 2(3) = 3
2y = 3 - 1 - 6 = -4
y = -2.
You might be interested in
Answer:
you didn't include a picture.
Step-by-step explanation:
if you want to include a picture I can try to help you
Number one would be x=4, I hope this helps
Answer:
D.
Step-by-step explanation:
[7^(-8)]^(-4) =
A power raised to a power: multiply the exponents.
= 7^[(-8)*(4)]
= 7^(32)
Answer: D.
Answer:
-0.663
Step-by-step explanation:
-38/180 × pi = -0.6632251158
13c-22=-17c+14
-14 -14
13c-36=17c
-13 -13
-36\4=4\42
C=-9